Biomass Juncus Derived Nitrogen-Doped Porous Carbon Materials for Supercapacitor and Oxygen Reduction Reaction - He, Guanghua; Yan, Genping; Song, Yonghai; Wang, Li (Frontiers in Chemistry, 2020)
Juncus is a perennial herb aquatic plant found worldwide, with high reproductive ability in warm regions. It has three-dimensional hierarchical porous triangular networks structures composited of tubular fibers. Here, juncus derived nitrogen-doped porous carbon (NDPC) was prepared by mixing juncus and ZnCl2 through one-step pyrolysis and activation which is a low-cost, simple, and environmentally friendly method. The NDPC had hierarchical porous structures and a high specific surface area and was applied for supercapacitor and oxygen reduction reaction (ORR). The resulted NDPC-3-800 was prepared by mixing juncus with ZnCl2 at a mass ratio of 1:3 and then carbonized at 800°C, it was used as electrode material of a supercapacitor. The supercapacitor exhibited excellent specific capacitance of 290.5 F g−1 and 175.0 F g−1 in alkaline electrolyte at the current densities of 0.5 A g−1 and 50 A g−1, respectively. The supercapacitor showed good cycle stability, and the capacitance was maintained at 94.5% after 10,000 cycles. The NDPC-5-800 was prepared by mixing juncus with ZnCl2 at a mass ratio of 1:5 and then carbonized at 800°C. It exhibited outstanding ORR catalytic activity and stability attributing to their high specific surface area and abundant actives sites. The juncus can derive various materials for application in different fields.